Certain issues of legislative regulation of digitalization of healthcare in Kazakhstan - Tazhiyeva, M.N.; Mytalyapova, A.Sh. (Karagandy University of the name of academician E.A. Buketov, 2025)
The aim of the work is to identify the imperfections of legal regulation that hinder the realization of the right to health care through the digital format of receiving medical services. To consider this topic, the authors studied the norms of national legislation affecting the processes of informatization of all spheres of the economy and digitalization of health care, in particular, through system analysis, comparative-legal and formallegal methods. As a theoretical basis, the authors studied legal scientific literature, documents of international organizations devoted to the subject of the study. In conclusion, the authors highlight the significant role of protection of personal medical data and principles of ethical application of artificial intelligence in the regulation of social relations in the field of digitalization of health care and the need to revise and harmoniously combine the norms of different legal acts regulating the digital development of health care.
Қазақстандағы денсаулық сақтау саласын цифрландыруды заңнамалық реттеудің кейбір мәселелері
Отдельные вопросы законодательного регулирования цифровизации здравоохранения в Казахстане
Keywords: right to health care; digitalization of healthcare; regulation of healthcare digitalization; protection of medical data; artificial intelligence; ethical principles of AI; law on AI; digital code